Development of an Interactive E-Module for Human Digestive System Material - Namah, Indah Tamimun; Nugraha, Mohammad Fahmi; Permana, Rahmat (CV. Rayyan Dwi Bharata, 2023)
This research aims to develop a product in the form of Interactive E-Module media for Human Digestive System Material. This study uses the Research and Development method. This research was conducted at SDN Nagalintang. The results of the validation of the Interactive E-Module media were carried out by experts such as material experts, media experts and linguists. Each expert is as follows: the material expert gives a final score of 0.92 with the eligibility criteria of 92% or can be said to be